Evaluation of the Physical and Chemical Properties of Vehicles Brake Pad Particles - Ghaidan, Hajer Qais; Al-Easawi, Nada Abdulrahman F. (Iraqi Journal of Science, 2019)
Air pollution is a major environmental problem, due to the increasing number of vehicles in Baghdad city streets and their direct impact on the process of air pollution resulting from an exhaust and non-exhaust pollutants (brake, clutch, tire wear, road surface wear and corrosion of vehicle components). The aim of this study is to detect the chemical and physical properties of brake pad particles as well as the concentrations of heavy metals found in these pad particles. This study included, a collection of eleven (11) samples of brake pads belong to different types of cars, most of these cars were used commonly in Baghdad city streets. The size of break pads particles was examined under Scanning Electron Microscopy (SEM). The results showed that the brake pad particle size with diameters ranged (particle â‰¥ 0.5 Âµm). While the concentrations of metallic elements with oxide form (Al, Sb, Cr, Cu, Cd, Fe, Pb, Mg, Mo, Ni, Si, S, Sn, and Zn) which examined in X-ray Fluorescence Spectroscopy (XRF), indicated high concentrations of (Fe> Cu > Si > S >Sb> Zn > Mg > Al >Sn> Cr > Mo) respectively and other examined elements concentrations within the range of World Health Organization (WHO).